Production potential and economics of crop sequences for aonla (Emblica officinalis Gaertn.) based agrihorticultural system under rainfed condition - Patle, Naveen; Upadhyaya, S.D.; Bansal, Shikha (Indian Journal of Agroforestry, 2020)
The field experiment was conducted at farmer’s field in Jabalpur district (Madhya Pradesh) in six year old aonla (cv. NA 7) plantation from kharif 2011 to summer 2013 in two consecutive seasons to assess the performance of aonla based agrihorticultural system under rainfed condition. The results reveal that reduction in seed yield of soybean with aonla over sole cropping was 25.00, 10.30 and 7.33% in aonla + soybean - wheat, aonla + soybean – gram and aonla + soybean - mustard, respectively. The yield of pigeon pea reduced by 12.1% in aonla + pigeon pea – gram; 11.2% in aonla + pigeon pea - wheat; and 11.7% in aonla + pigeon pea - black gram as compared to their respective sole cropping. The average decrease in seed yield of mustard in aonla + soybean - mustard over the soybean - mustard was of the order of 3.2%. The economic analysis of different cropping system showed that higher returns were obtained when the intercrops were grown in association with aonla rather than sole cropping. Intercropping of soybean - gram and soybean - mustard crop sequences with aonla gave highest fruit yield of aonla along with gross monetary return. However, soybean grown in rotation with mustard earned maximum net returns (Rs. 95,310/ha), followed by soybean – gram (Rs. 87,960/ha), pigeon pea - black gram (Rs. 81,800/ha) and pigeon pea – gram (Rs. 79,900/ha). Various cropping sequences when intercropped with aonla resulted in an additional income varying from Rs. 53,140/ha (aonla + pigeon pea - wheat) to Rs. 75,450/ha (aonla + soybean - mustard). Aonla intercropped with soybean - mustard also recorded the highest benefit: cost ratio of 4.02 followed by aonla intercropped with aonla + pigeon pea - black gram (3.73), aonla + pigeon pea - gram (3.38) and aonla + soybean - gram (3.22). The sole crop of aonla gave benefit: cost ratio of 2.59 only.